Filling in the Blanks: What Restaurant Patrons Assume About Missing Sanitation Inspection Grades. Issue 3 (July 2020) - Gurney, Nikolos; Loewenstein, George
How do people respond when decision-relevant information is withheld by sellers? The authors address this general question by examining how prospective diners respond when sanitation inspection grades (SIGs) are not reported by a restaurant. Despite disclosure mandates in some municipalities, SIGs are not always available when dining choices are made, especially when food is ordered for delivery. After documenting participants' failure to discount appropriately for a missing SIG, the authors demonstrate, through a series of follow-up studies, the robustness of the phenomenon in the face of interventions designed to increase the salience of the missing information. The authors find evidence of increased discounting, however, in a study designed to draw attention to the missing information via a side-by-side comparison of restaurants that did and did not provide SIGs.